2023
DOI: 10.7759/cureus.40014
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitudes, and Practices Regarding Brucellosis in Taif City, Saudi Arabia

Faisal K Al-homayani,
Fai M Altalhi,
Zohour A Almalki
et al.

Abstract: Background: Brucellosis is a serious zoonotic infectious disease. Humans contract the disease by coming into contact with infected animals or their products. In Saudi Arabia, brucellosis is considered to be an endemic disease, with an annual incidence of 15.34 per 100,000 population from 2003 to 2018. Because of the devastating consequences for human health, raising awareness is an essential component in preventing brucellosis. Our study aims to assess the knowledge, awareness, and attitudes regarding brucello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…These results resemble findings from a similar study from Jordan (14). Meanwhile, the studies on the Saudi public revealed that 53.1-90% exhibited good knowledge of brucellosis, with gender, age, and education level influencing awareness (9)(10)(11)(12). The significant association between higher educational levels and good knowledge of brucellosis reported in these studies was similar to our opposite finding that lack of education was associated with poor knowledge.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results resemble findings from a similar study from Jordan (14). Meanwhile, the studies on the Saudi public revealed that 53.1-90% exhibited good knowledge of brucellosis, with gender, age, and education level influencing awareness (9)(10)(11)(12). The significant association between higher educational levels and good knowledge of brucellosis reported in these studies was similar to our opposite finding that lack of education was associated with poor knowledge.…”
Section: Discussionsupporting
confidence: 88%
“…Our study found that most participants have heard of brucellosis (91.4% of farmers, 95.8% of commercial owners, and 98.2% of private owners). These percentages exceeded those came from studies that assessed the awareness of the Saudi public of brucellosis, where four studies from different regions involving 311 to 1,244 participants (with a collective total of 3,353 participants) found that only more than half of the surveyed populations were aware of the disease (range 50-73.6%) (9)(10)(11)(12). This shows that brucellosis is widely known in Saudi Arabia; though, people working with animals were more likely to have heard of it.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…It may also be characterized by the detection of urine albumin with an excretion rate over 300 mg per 24 hours [1] . CKD impacts around 5-10% of the global population, with an estimated annual incidence rate of around 5-8% [2] . Chronic kidney disease-mineral bone disorder (CKD-MBD) is a systemic disease that affects the whole body.…”
Section: Introductionmentioning
confidence: 99%